Penentuan Kondisi Optimum Penyerapan Logam Kadmium Oleh Asam Humat - Darmokoesoemo, Handoko; Setyawati, Harsasi (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
This research was study on the formation of complexes between metals Cd(II) with humic acid and the optimum conditions of metal Cd(II) adsorption by humic acid. Determination of optimization conditions of metal Cd(II) adsorption by humic acid i.e. variation of contact time, pH and Cd(II) concentration. The results showed the optimum contact time was 90 minutes with a percentage of Cd adsorped was 86.52%, the pH optimum was pH 6 with a percentage of Cd adsorped was 80.39% and the optimum Cd(II) concentration was 500 ppm with the optimum Cd(II) adsorped by humic acid was 221, 8 mg /L. FTIR analysis showed the presence a bond between the metal Cd(II) with oxygen groups of humic acid at wavelength of 354.90 cm-1. The adsorption model of Cd(II) by humic acids showed Langmuir type with correlation coefficient 0,99909.Keywords : humic acid, cadmium, Cd(II)-humat complexes.